Tekanan kerja dan faktor-faktor stres dalam kalangan guru sekolah rendah di Jitra, Kedah - Amelia, Ibrahim (2018)
Pressure refers to the formation of the behaviour as well as affecting the emotions of an individual. This study was conducted to identify the level of stress faced by the teacher and to examine the factors contributing to the problem of working stress among current teachers. The main objective is to examine the level of teacher pressure and thus see the relationship between the level of pressure faced with factors identified by the researcher. This study involved 220 teachers from three primary schools in Jitra district of Kedah. Of the 220 sets of questionnaires that have been distributed by the researchers only 120 sets have been successfully restored. The set of questionnaire consists of 39 items using a seven-point likert scale. Each hypothesis was tested using Statistic Package for Social Science (SPSS) version 22.0. The data obtained were analysed by using descriptive analysis, collation and regression analysis. A total of five major hypotheses were formed after factor analysis was conducted by researchers. The findings of this study found that teachers experienced moderate pressure. Whereas, the results of the coloration analysis found that the workload factor, time constraints, bad relationships between teachers and pupils, principals' support had a positive correlation to teacher work stress. However, co-workers 'factors are not related to teachers' work stress. Furthermore, the results of regression analysis found that the factors that showed the strongest influence on teacher work pressure were time constraints and burden of tasks. While the relationship factor between teacher and student shows a correlation to the simple level. Co-factor factors have show weak relationships and principals' support has no relationship with teacher work pressure.